The print in early modern England : an historical oversight - Jones, Malcolm, 1953-; Paul Mellon Centre for Studies in British Art. (New Haven [Conn.] : Published for the Paul Mellon Centre for Studies in British Art by Yale University Press, 2010)
This book provides an iconographic survey of the single-sheet prints produced in Britain during the early modern era and brings to light some very recent discoveries. This large body of material is treated thematically, and within each theme, chronologically. Chapters are devoted to portents and prodigies, the formal moralities and doctrines of Christianity, the sects of Christianity, and the often vicious satire of the Catholic confession (but also of Protestant non-conformists) visual satire of foreigners and others, domestic political issues principally, the English Civil War social criticism and gender roles, marriage and sex, as well as numerical series and miscellaneous visual tricks, puzzles and jokes. The concluding chapter considers the significance of this wealth of visual material for the cultural history of England in the early modern era.
Introduction: the circulation and use of prints -- Numbered series -- Emblematic diagrams and schemata -- At home and abroad: the Tudors and early Stuarts -- 'These distempered times': the Civil War period -- At home and abroad: the later Stuarts -- Doctrinal opponents: anti-Catholic satire -- Doctrinal opponents: anti-Protestant and anti-sectarian imagery -- The Godly life -- Sinful pleasures, I: folly -- Sinful pleasures, II: lust -- 'Lerning us to beware': portents and prodigies -- Death and judgement -- A topsy turvy world -- The place of women -- A picture of society.
Includes bibliographical references and index.
Keywords: Prints, English -- 16th century -- Themes, motives; Prints, English -- 17th century -- Themes, motives; Art and society -- England -- History -- 16th century; Art and society -- England -- History -- 17th century